2018
DOI: 10.1002/jcp.27176
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Sendai virus strain Tianjin induces apoptosis and autophagy through reactive oxygen species production in osteosarcoma MG‐63 cells

Abstract: Sendai virus strain Tianjin, a novel genotype of Sendai virus, has been proven to possess potent antitumor effect on certain cancer cell types although inactivated by ultraviolet (UV). This study was carried out to investigate the in vitro anticancer properties of UV-inactivated Sendai virus strain Tianjin (UV-Tianjin) on human osteosarcoma cells and the underlying molecular mechanism. Our studies demonstrated UV-Tianjin significantly inhibited the viability of human osteosarcoma cell lines and triggered apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
1
5
1
Order By: Relevance
“…However, the molecular mechanisms for the anticancer activity of SeV are poorly understood. Our latest study showed that UV-Tianjin, a new genotype of SeV, significantly suppressed the proliferation of HOS cells in a dose-dependent manner (Han et al 2019). In the present study, we found that UV-Tianjin had no significant effect on the viability of human osteoblasts hFOB1.19, indicating a strong selective effect of UV-Tianjin towards cancer cells.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…However, the molecular mechanisms for the anticancer activity of SeV are poorly understood. Our latest study showed that UV-Tianjin, a new genotype of SeV, significantly suppressed the proliferation of HOS cells in a dose-dependent manner (Han et al 2019). In the present study, we found that UV-Tianjin had no significant effect on the viability of human osteoblasts hFOB1.19, indicating a strong selective effect of UV-Tianjin towards cancer cells.…”
Section: Discussioncontrasting
confidence: 39%
“…Our previous study has shown that treatment with UV-Tianjin for 24 h resulted in a significant dose-dependent decrease in cell viability of HOS cells by MTT assay (Han et al 2019). In the present study, the effect of UV-Tianjin on the viability of human osteoblasts hFOB1.19 was examined.…”
Section: Uv-tianjin Had No Significant Effect On the Viability Of Hummentioning
confidence: 79%
See 1 more Smart Citation
“…Inactivated Sendai virus (ISV) was found to induce ROS-dependent apoptosis and autophagy in human prostate cancer cells ( Qian et al., 2018 ). ISV strain Tianjin also induces apoptosis and autophagy through generation of reactive oxygen species in osteosarcoma MG-63 cells ( Han et al., 2019 ).…”
Section: Oncolytic Viruses-modulated Apoptosis Autophagy Syncytium Fo...mentioning
confidence: 99%
“…Non-small cell lung cancer accounts for approximately 85% of all diagnosed lung cancers. 1 Currently, chemotherapy is still the major treatment method for the control of NSCLC, and platinum-based chemotherapy, such as cisplatin, is widely recommended for advanced patients. However, cisplatin treatment can result in cancer cell drug resistance, which limits the clinical application of cisplatin.…”
Section: Introductionmentioning
confidence: 99%